The Case for a Long-Run Inflation Target of Four Percent - Ball, Laurence (IMF Working Papers; Working Paper ;, 2014)
Many central banks target an inflation rate near two percent. This essay argues that policymakers would do better to target four percent inflation. A four percent target would ease the constraints on monetary policy arising from the zero bound on interest rates, with the result that economic downturns would be less severe. This benefit would come at minimal cost, because four percent inflation does not harm an economy significantly.